Modelling the Effect of the Competitive Environment on Brand Performance of the Sports Goods with the Mediating Role of Marketing Strategies - Roghayeh Sarlab; Zahra Alipour Nadinluoi; Shahin Babanzadeh (Shahid Bahonar University of Kerman, 2020)
The aim of this paper was to investigate the effect of the competitive environment on brand performance of the sports goods with the mediating role of marketing strategies in Iran. The statistical population of the study consisted of managers, staff, distributors, shop assistants, manufacturers of Iranian sports goods and sport products in Tabriz. 150 subjects were studied through total sampling approach and completed the questionnaire. Structural equation modeling were conducted for data analysis. The results showed that: a) there is a positive and significant relationship between competitive environment and brand performance, b) there is a positive and significant relationship between competitive environment and the marketing strategy, and c) there is a positive and significant relationship between marketing strategies and the brand performance. The findings also demonstrated that the research model has an appropriate fitness.